HER3 expression is correlated to distally located and low-grade colon cancer. (2nd July 2016) - Lédel, Frida; Stenstedt, Kristina; Hallström, Marja; Ragnhammar, Peter; Edler, David
Abstract: Background HER3 is a member of the human epidermal growth factor receptor complex (EGFR, HER2, HER3 and HER4). It has been investigated as a prognostic biomarker in colorectal cancer but is sparingly studied in colon cancer. HER3 can affect cellular proliferation, differentiation and migration in oncogenesis through ligand binding and activation of intracellular signal pathways. Recently, we found that expression of cell surface HER3 can be detected at a high extent in primary colorectal tumors, lymph node and liver metastases and that it correlated with poor prognosis. This large, explorative, retrospective study evaluates the prognostic value of HER3 in colon cancer and the association of HER3 to tumor location.Material and methods . Immunohistochemical detection with a monoclonal HER3 antibody in primary colon tumors of stage II and III, from 521 patients, was performed.Results HER3 was expressed at high levels in 67% of the colon tumors. High HER3 expression was associated with distal tumor location ( p  < 0.0001) and low-grade tumor ( p  < 0.0001). In the group of patients with distal colon cancer (230/521), HER3 expression correlated to shorter disease-free survival (DFS) ( p  = 0.03) in the univariate analysis and in the multivariate analysis, a hazard ratio of 0.56 (95% CI 0.31–0.99) ( p  = 0.047) was observed.Conclusion In this explorative, retrospective study, high HER3 expression in colon cancer was associated to distal colon location and low-grade tumor. High HER3 expression was of prognostic value according to DFS in distal colon cancer in univariate and multivariate analysis. We could not find a significant value of HER3 expression with respect to overall survival (OS).